PEDIATRIC HEADACHE: A DIAGNOSTIC APPROACH BASED ON RED FLAGS (REMUNOM, 2026)
Headache is one of the most common neurological complaints in children and adolescents, representing a frequent reason for medical consultation. Although most cases correspond to primary headache disorders, a minority may be associated with serious underlying conditions requiring prompt diagnosis. Distinguishing between primary and secondary headache remains a major challenge in pediatric clinical practice. This study aims to present a structured and evidence-based diagnostic approach to pediatric headache, emphasizing the identification and interpretation of red flags and the appropriate use of neuroimaging. A narrative review of the literature was conducted, including studies published between 2010 and 2024 in major databases. Red flags such as abnormal neurological examination, progressive headache pattern, persistent vomiting, seizures, and signs of intracranial hypertension are strongly associated with secondary causes. However, their predictive value varies, and isolated findings often lack specificity. Evidence suggests that combining multiple clinical variables improves diagnostic accuracy. Neuroimaging should not be routinely performed in children with recurrent headache and normal neurological examination, with magnetic resonance imaging being the preferred modality when indicated. A systematic and probabilistic approach—integrating clinical history, neurological examination, contextual interpretation of red flags, and judicious use of imaging—allows clinicians to optimize diagnostic accuracy while minimizing unnecessary interventions. This approach is essential to ensure patient safety and efficient use of healthcare resources.